Analisis Masukan dan Proses Asuhan Pelayanan Nifas oleh Bidan Pelaksana di Wilayah Dinas Kesehatan Kota Semarang Tahun 2014 - Sri Wahyuni (M); Sri Achadi N; Atik Mawarni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
Postpartum care coverage in the city of Semarang in 2011-2013 increased but has not reached the target of 90%. Based on preliminary survey results indicate that postpartum care services performed by midwives implementers in the region of Semarang City Health Office was not maximized. The purpose of this study is to explain how the inputs and processes of postpartum care services in the area of Semarang City Health Office. This study was qualitative, data was collected through in-depth interviews and observation. The main informants were 2 the service of a midwives of 2 community health centers that have coverage postpartum visits highs and lows. Informant triangulation was 2 coordinator of midwives and 2 manager of community health center of 2 health centers health centers that have coverage postpartum visits highs and lows. Data were analyzed using content analysis. The results showed that the implementation of aspects of care inputs: human resources quantity is still less number of midwife. in quality, midwives knowledge about postpartum care less, and policies for the implementation of appropriate postpartum care standards yet exist. The assessment was not carried out fully. Diagnosis was not appropriate nomenclature, planning has not been written in the book CM. Implementation of care has not been done comprehensively. It is recommended to the Department of Health to: conduct refresher midwifery knowledge and skills regarding the appropriate standard of care post-partum care, facilitates the recording form appropriate standard of care post-partum care, and monitoring and provide SOP on postpartum care.